REVIEW ON RAW MATERIAL INVENTORY PLANING AND CONTROL OF SMALL CRAB AT PT. TOBA SURIMI INDUSTRIES MEDAN INDUSTRIAL ESTATE (KIM) II DELISERDANG - ROSMAINI, ROSMAINI (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2014)
PT. Toba Surimi Industries is a company that operated in sea product processing and export. One of exported product is processed and frozen pasteurized small crab. The small crab is important raw material for company as a determining factor of the production process and selling. The obstacle faced by PT. Toba  Surimi Industries in supply of raw material is  the scarce of crab as seasonal product and depend on the supplier. Therefore, PT. Toba Surimi Industries buys the crab in big volume that causes the number of inventory over than the required material. This condition causes the higher of investment in inventory. Based on this condition, the problem formulation are (1) What the raw material inventory planning and control  of the small crab by PT. Toba Surimi Industries, (2) How the company do the raw material inventory planning and control in order to avoid over or under inventory level.  The objective of this research are (1) to study the raw material inventory planning and control of small crab applied by company, (2) to design effective inventory planning and control  to avoid the over or under raw material inventory. Based on the estimation of export volume of small crab using Montecarlo simulation method, the company can use it as input to predict the future selling volume and to determine the required raw material.